Pengaruh Kepadatan Terhadap Pertumbuhan dan Kelulushidupan Juvenil Kerang Mutiara (Pinctada margaritifera) Diperairan Desa Tanah Merah, Kabupaten Kupang - Putra, Asry R; Santoso, Priyo; Rebhung, Felix (Nusa Cendana University, 2024)
Pearl mussels are included in commodities that almost all parts of the body can be utilized. Starting from the pearls produced, pearl clam shells, and pearl clam meat have a selling value in the market. In addition, pearl mussels (Pinctada margaritifera) have a delicious taste and have a high enough protein content to become a target for public consumption. The cultivation of this type of pearl mussel is still very little, and the utilization of this type of pearl mussel still relies on nature, this certainly has the potential for a decrease in its population in nature. This study aims to determine the effect of density on the growth rate and survival of pearl mussel juveniles (Pinctada margaritifera). This study used treatment A (8 individuals/basket), treatment B (12 individuals/basket), treatment C (16 individuals/basket), treatment D (20 individuals/basket). The results of the analysis conducted showed no significant difference (P> 0.05) in the growth and survival of pearl mussels (Pinctada margaritifera). The research was conducted for 2 months in the waters of Tanah Merah Village, Kupang Regency. Keywords: Density, Pearl mussels (Pinctada margaritifera), Absolute Growth, Survival